PERBEDAAN HASIL JAHITAN GAUN MENGGUNAKAN POLA PRAKTIS DAN POLA MEYNEKE PADA SISWA KELAS XI - Yasinta Wea Ari (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2020)
The purpose of the research is to know the difference in the results of the stitches to make dress using Practical pattern and Meyneke pattern. Type of research used in this study is Quasi Experiment. Validity test using the formula Aikens V obtained 22 valid items and reliability testing using the consistency between rater obtained rater 1 =85 and rater 2 =82. Descriptive research results indicate that the tendency of the stitching results using a Practical pattern has Mean value of 148.27, and Meyneke pattern has Mean value of 152.40. Value of the t test, obtained tcount = -1,517 and ttable at the 5% level with df = 19, which is 2.093 (tcount <ttable), it means there are no positive and significant differences between the results of the stitching of the dress using the Practical and Meyneke pattern of the XI grade students of Karya Rini Vocational High School, Yogyakarta.